Examining Profitability as a Mediating Factor in the Relationship Between Capital Structure, Liquidity, and Sales Growth on Firm Value - Novita Ramadhanfi Maulani; Fitriyah Fitriyah; Maretha Ika Prajawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
The objective of this study is to analyze and assess the role of profitability as an intervening variable in the connection between capital structure, liquidity, and sales growth on the firm value. This research uses a purposive sampling methodology to choose a sample of 13 companies within the healthcare sector. The analysis is executed through path analysis employing the EViews version 12 application. Research findings, shows that capital structure does not influence profitability, while liquidity and sales growth indeed influence profitability. Capital structure, liquidity, and sales growth do not affect firm value, but profitability does. Additionally, profitability does not serve as an intermediary in the connection between capital structure, liquidity, and sales growth in affecting firm value. This research provides a theoretical contribution by examining how profitability acts as an intermediary variable within the framework of the connection between capital structure, liquidity, and the role of sales growth in affecting the firm value in the healthcare sector during the period 2020-2023. This provides a new understanding of the specific internal financial mechanisms in the healthcare sector, especially in pandemic-affected conditions, which have not been studied in depth in the financial literature.